Internet addiction continuum and its moderating effect on augmented reality application experiences: digital natives versus older users. Issue 1 (2nd January 2023) - Stangl, Brigitte; Kastner, Margit; Park, Sangwon; Ukpabi, Dandison
ABSTRACT: Problematic online usage (POU) and Internet addiction (IA) lack a refined classification. Using 796 questionnaires, this study is the first to reveal a continuum ranging from Casual users (i.e. older users) to Addicts (i.e. digital natives) acknowledging five different severity levels of POU to IA. Depending on where users are located within the addiction continuum, usability of augmented reality (AR) applications has different effects. Most interestingly, the experience of Casual users is triggered by enjoyment, whilst enjoyment exerts a negative effect on the emotional and action experiences of Addicts-in-denial. The study provides actionable implications for IA, POU, and AR behaviour.